Reconstructing the Jihad in Contemporary Islamic Law: An Analysis of the Sheikh Ahmad al-Tayyeb’s Thought - Ainudzaky, Muhammad; Musdalifa, Musdalifa; Nisa, Khoirun; Fiqar, Mujahid Sam Dzul (Ma’mal: Jurnal Laboratorium Syariah dan Hukum, 2025)
Today's jihad discourse is polarized in meaning, between ethical-spiritual understanding and militaristic reductionism that is often associated with violent extremism. This study aims to examine how Sheikh Ahmad al-Tayyeb reconstructed the meaning of jihad normatively and contextually, and assess its implications for the development of contemporary fiqh. This research is a literature study with a normative-conceptual approach and analysis of maqāṣid al-sharī'ah. Primary data are obtained from al-Tayyeb's works, fatwas, and official statements as well as documents, while secondary data are derived from classical fiqh literature and contemporary studies of jihad. The analysis is carried out in a descriptive-analytical and critical manner to identify the conceptual construction of jihad and its relevance in the modern context. The results of the study show that al-Tayyeb interprets jihad as a comprehensive effort to uphold justice, maintain human dignity, and protect the public interest. The qitāl dimension is recognized in a defensive framework and is limited by state authority as well as universal humanitarian principles. In practice, jihad is realized through education, moderate da'wah, interreligious diplomacy, and global humanitarian solidarity. This reconstruction contributed to a more contextual, moderate, and harmonized fiqh jihad renewal without abandoning the normative foundations of the Islamic tradition.